2014
DOI: 10.11591/ijphs.v3i3.4692
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Immunization Defaulting among Children Age 12-23 Months in Hawassa Zuria District of Southern Ethiopia: Community Based Unmatched Case Control Study

Abstract: <p>As part of the overall package of maternal and child health services in Ethiopia, all children are provided with free immunization services and it is available in all government health facilities, both in rural and urban areas. But significant number of children was defaulted from Immunization schedule, even after the health extension program was launched. Therefore, the study was assessed predictors of immunization defaulting among children age range of 12-23 months, in Hawassa Zuria district of sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 3 publications
(3 reference statements)
2
10
0
Order By: Relevance
“…This finding aligns with our current understanding of the relationship between wealth and immunizations from Uganda [15], Ghana [29], and 31 countries in sub-Saharan Africa [30]. Furthermore, though the relationship between timeliness and wealth has not been explored previously in Ethiopia, the literature does suggest that wealth is associated with other measures of vaccination, e.g., complete vaccination coverage and defaulting from the vaccination program [4,5,3133]. The strength of the association between other socioeconomic variables and timeliness of vaccination for these birth doses differed depending on whether the child was born at home or at an institution.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding aligns with our current understanding of the relationship between wealth and immunizations from Uganda [15], Ghana [29], and 31 countries in sub-Saharan Africa [30]. Furthermore, though the relationship between timeliness and wealth has not been explored previously in Ethiopia, the literature does suggest that wealth is associated with other measures of vaccination, e.g., complete vaccination coverage and defaulting from the vaccination program [4,5,3133]. The strength of the association between other socioeconomic variables and timeliness of vaccination for these birth doses differed depending on whether the child was born at home or at an institution.…”
Section: Discussionsupporting
confidence: 82%
“…We do note that there is still a rural-urban discrepancy in the expected time to vaccination, with urban children taking less time compared to rural children, even for the group of children born at an institution. This association between wealth and timeliness may be due to challenges in healthcare access faced by poorer families and possible institutional barriers that individuals from certain ethnic groups face; while the vaccines are provided for free, families still must be able to afford transportation to the health center and lost productivity from taking their child to the clinic instead of working [5,31].…”
Section: Discussionmentioning
confidence: 99%
“…The appointment reminder system may have contributed to reducing defaulters by creating a forum for health workers to provide MNCH education to mothers. Studies have shown fewer defaults and higher immunization completion when caregivers discussed immunization with HEWs [ 10 ] or other families in the community [ 19 ]. In addition, caregivers who were visited at home by HEWs have been shown to have better immunization completion rates [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, caregivers who were visited at home by HEWs have been shown to have better immunization completion rates [ 20 ]. Use of maternal health services has also been associated with completion of immunizations [ 7 , 10 ]. The FCP promoted the use of ANC with the Enat Mastawesha and supported the EPI system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation